HISTOPATHOLOGICAL CHANGES OBSERVED IN THE SPLENIC TISSUES OF THE FISH Clarias batrachus on EXPOSURE TO THE PESTICIDE ROGOR - SHARAN, NANDINI; KUMAR, PAWAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Present study focuses on the effect of Rogor induced histological alteration in the spleen tissues of freshwater fish Clarias batrachus more commonly called Mangur. The lethal concentration50 of the pesticide Rogor was calculated which came out to be 4 µl/L. Then, solution of the two sub lethal concentration were prepared in distilled water .The lower and upper sub lethal concentrations were taken as 1 µl/L and 2.5 µl/L respectively. Fishes were grouped in three; first were exposed to lower sub lethal concentration, the second were exposed to higher sub lethal dose and the third were the controlled fishes. Groups consisted of 10 fishes each. Fishers were sacrificed for the experimental protocol on the 5th, 10th and 15th day of exposure to the pesticide. The splenic tissues of fishes from all three groups were dissected and then kept in 10% formalin. They were cut in small pieces and were fixed in neutral formalin solution and light microscopy was performed. The light micrograph was stained with hematoxylin and eosin that showed its parenchymatic components. Seven plates were observed under a low and high power.1st plate was of tissues of controlled fishes. Three plates were of concentration 1 µl/L and three were of 2.5 µl/L each, observed on the 5th, 10th and 15th day of exposure. In controlled fishes under lower and higher power, the red and white pulp enclosed in a capsule, melanomacrophages, distinct trabaculae and blood vessels were observed .In the present work, sub lethal exposure of rogor induced many histopathological anomalies in the spleen, viz. Dissolution of the white pulp, aggregation of more melanomacrophage , autolysis of RBCs and loss of cellular architecture and matrix and distinct ridge formation. Hence, the experimental protocol displayed the alteration of the normal tissues of spleen of fish thereby showing the toxic impact of the pesticide.